1EXPERIENCE RESULTS OF SOFTENING DISC NEAR THE GRADER SCOOP - Kuchkarov Jurat Jalilovich; Olmasov Sukhrob Xurshid uglu; Khudoydotov Ramazon Uchkunjon uglu; Azimova Guzal Adizovna (Journal of new century innovations, 2023)
Abstract: The article presents the results of laboratory experiments to determine the productivity and some other parameters of the disk working body, working with the scheduler bucket in order to improve the process of leveling fields that meet the agrotechnical requirements of pre-sowing background.